2015
DOI: 10.1016/j.rbre.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of anticoagulation in the treatment of thrombosis in the antiphospholipid syndrome: a meta-analysis

Abstract: RBRE-155; No. of Pages 8 r e v b r a s r e u m a t o l . 2 0 1 5;x x x(x x):xxx-xxx REVISTA BRASILEIRA DE REUMATOLOGIA w w w . r e u m a t o l o g i a . c o m . b r Thrombosis Hemorrhage Warfarin a b s t r a c t Introduction: Discussion about the intensity of warfarin in patients with antiphospholipid syndrome (APS) remains present in our days. Objectives: To evaluate which intensity of anticoagulation with warfarin is associated with a greater reduction of thromboembolic events in the treatment of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…2 Currently, it is recommended that a target international normalized ratio (INR) of 2.5 (range, 2–3) is maintained for an indefinite period following the first episode of venous thromboembolism, 3,4 although in patients with APS with recurrent thrombosis or arterial thrombosis, the optimal intensity of anticoagulation is an issue of debate. 5 Direct oral anticoagulants (DOACs) represent an attractive therapeutic option. These pharmacological compounds directly inhibit a single enzyme in the coagulation cascade.…”
Section: Introductionmentioning
confidence: 99%
“…2 Currently, it is recommended that a target international normalized ratio (INR) of 2.5 (range, 2–3) is maintained for an indefinite period following the first episode of venous thromboembolism, 3,4 although in patients with APS with recurrent thrombosis or arterial thrombosis, the optimal intensity of anticoagulation is an issue of debate. 5 Direct oral anticoagulants (DOACs) represent an attractive therapeutic option. These pharmacological compounds directly inhibit a single enzyme in the coagulation cascade.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the patients who rapidly achieved the rst therapeutic INR target of warfarin were more likely to experience an increased risk of supratherapeutic INR. Since there is a strong relationship between the supratherapeutic INR and the risk of bleeding during warfarin treatment [27], it is recommended to closely monitor INR levels in patients rapidly achieving the rst therapeutic INR.…”
Section: Discussionmentioning
confidence: 99%
“…Na presente revisão sistemática, os estudos foram classificados como de alta qualidade metodológica quando apresentaram pontuação igual ou maior que 70% na escala (cerca de 8 pontos para estudos transversais), seguindo critérios adotados por outros autores em artigos de revisão sistemática (THIENGO et al, 2011;CARVALHO, 2015). As divergências entre os revisores foram resolvidas por consenso (Tabela 1).…”
Section: 4 a V A L I A ç ã O D A Q U A L I D A D E M E T O D O L ó unclassified